The roles of antimicrobial peptide, rip-thanatin, in the midgut of Riptortus pedestris. (January 2018) - Park, Kyoung-Eun; Jang, Seong Han; Lee, Junbeom; Lee, Seung Ah; Kikuchi, Yoshitomo; Seo, Young-su; Lee, Bok Luel
Abstract: Recently, we have reported the structural determination of antimicrobial peptides (AMPs), such as riptocin, rip-defensin, and rip-thanatin, from Riptortus pedestris . However, the biological roles of AMPs in the host midgut remain elusive. Here, we compared the expression levels of AMP genes in apo-symbiotic insects with those of symbiotic insects. Interestingly, the expression level of rip-thanatin was only significantly increased in the posterior midgut region of symbiotic insects. To further determine the role of rip-thanatin, we checked antimicrobial activity in vitro . Rip-thanatin showed high antimicrobial activity and had the same structural characteristics as other reported thanatins. To find the novel function of rip-thanatin, rip-thanatin was silenced by RNA interference, and the population of gut symbionts was measured. When rip-thanatin was silenced, the symbionts' titer was increased upon bacterial infection. These results suggest that rip-thanatin functions not only as an antimicrobial peptide but also in controlling the symbionts' titer in the host midgut. Highlights: The expression of rip-thanatin was mediated by gut symbiont. The rip-thanatin showed high antimicrobial activity against E. coli and S. aureus . The population of symbionts was increased in rip-thanatin -silenced insect upon bacterial infection.